Declining prevalence of cytological squamous intraepithelial lesions of the cervix among women living with well‐controlled HIV – Most women living with HIV do not need annual PAP smear screening. (19th September 2017) - Aho, Inka; Kivelä, Pia; Haukka, Jari; Sutinen, Jussi; Heikinheimo, Oskari
Abstract: Introduction: Cervical screening by means of annual Papanicolaou (PAP) smears has been recommended for all women living with HIV. We analysed the results of our annual PAP smear screening program to identify low‐risk subgroups for less rigorous screening. Material and methods: The study comprised 369 women followed at the Helsinki University Hospital 2002–2013, with a total of 2033 PAP smear results. We analyzed the temporal changes in PAP smear findings. Logistic regression analysis for binominal dependent variables was used for assessing risk factors for ever having cytological squamous intraepithelial lesions (hereafter referred as SIL) using generalized estimating equations taking into account multiple observations of each patient. Results: Most women had well‐controlled HIV, especially towards the end of the study. PAP smear results improved substantially. At the time of each individual's last PAP smear, 90.0% of the findings displayed normal results. Conversely, the rate of SIL decreased from 16.8% to 4.6% from 2002 to 2013. In multivariate analysis the risk of SIL was significantly lower in women with consecutive normal PAP smear findings during the first two years of follow up [odds ratio (OR) 0.21, 95% confidence interval (CI) 0.10–0.45, p  < 0.001] and with CD4 counts >500 cells/μL (OR 0.11, 95% CI 0.05–0.26, p  < 0.001). Conclusions: Widespread use of combination antiretroviral therapy (cART) and systematic cervical screening has reduced the rate of abnormal PAP smears. It seems feasible to identify low‐risk women by combining HIV‐related information and PAP smear results. Screening low‐risk women living with HIV at three‐year intervals similar to HIV‐negative women appears justified.